Fixel-Based Analysis of White Matter Degeneration in Patients With Progressive Supranuclear Palsy or Multiple System Atrophy, as Compared to Parkinson's Disease - Nguyen, Thanh-Thao; Cheng, Jur-Shan; Chen, Yao-Liang; Lin, Yu-Chun; Tsai, Chih-Chien; Lu, Chin-Song; Weng, Yi-Hsin; Wu, Yi-Ming; Hoang, Ngoc-Thanh; Wang, Jiun-Jie (Frontiers in Aging Neuroscience, 2021)
Introduction: White matter degeneration may contribute to clinical symptoms of parkinsonism. Objective: We used fixel-based analysis (FBA) to compare the extent and patterns of white matter degeneration in different parkinsonian syndromes – including idiopathic Parkinson’s disease (PD), multiple system atrophy (MSA), and progressive supranuclear palsy (PSP). Methods: This is a retrospective interpretation of prospectively acquired data of patients recruited in previous studies during 2008 and 2019. Diffusion-weighted images were acquired on a 3-Tesla scanner (diffusion weighting b = 1000 s/mm2 – applied along either 64 or 30 non-collinear directions) from 53 patients with PD (men/women: 29/24; mean age: 65.06±5.51 years), 47 with MSA (men/women: 20/27; mean age: 63.00±7.19 years), and 50 with PSP men/women: 20/30; mean age: 65.96±3.14 years). Non-parametric permutation tests were used to detect intergroup differences in fixel-related indices – including fiber density, fiber cross-section, and their combination. Results: Patterns of white matter degeneration were significantly different between PD and atypical parkinsonisms (MSA and PSP). Compared with patients with PD, those with MSA and PSP showed a more extensive white matter involvement – noticeably descending tracts from primary motor cortex to corona radiata and cerebral peduncle. Lesions of corpus callosum were specific to PSP and absent in both MSA and PD. Discussion: FBA identified specific patterns of white matter changes in MSA and PSP patients compared to PD. Our results proved the utility of FBA in evaluation of implied biological processes of white matter changes in parkinsonism. Our study set the stage for future applications of this technique in patients with parkinsonian syndromes.